The Role of Ternate-Tidore Fmu in Empowerment of Kups in Hkm Ake Guraci in Marikrubu Kelahan Ternate City - Tamrin Salim; Muhammad Julham; Nur Asmi Faradilla Hi. Ali (Peneliti.net, 2023)
Forest Management Unit (KPH) is a government agency responsible for forest management. KPH has an important role in the formation, licensing and even assistance to the Social Forestry Business Group (KUPS). This study aims to determine the role of KPH towards KUPS in HKM Ake Guraci, Marikrubu Village, Ternate City, North Maluku. Data collection techniques were taken by means of field observations, interviews and documentation studies from several related literature. The results of this study indicate that the Ternate-Tidore FMU played an important role in the formation of 6 KUPS at HKM Ake Guraci. Of the six KUPS, there are four KUPS that have carried out production activities, even KUPS Gosora which produces Candy and Selei Nutmeg has entered the stage of applying for a permit from the Food and Drug Administration (BPOM). Meanwhile, two KUPS are still not running as a result of the institutional factors of the KUPS itself.